Public Procurement as an Instrument for Transparency and Competition of Public Procurement - Carla Sofia Alves Lopes (2021)
Public procurement fosters the development of States, promoting economic efficiency and the promotion of social and environmental good. Public procurement is an instrument of administrative action to satisfy collective needs, but also a strategic instrument for governments. This type of contracts refers to economically and socially relevant acquisitions, interferes with job creation and encourages investment, and is highly relevant in the national budget, representing 4.18% of Portuguese GDP in 2019. The present study intends to analyse public procurement, in the last decade, regarding the transparency of public procurement procedures and the promotion of competition between economic operators in the attainment of the public interest. For this purpose, we use the qualitative methodology, which includes document analysis of public procurement reports from the Institute of Public Procurement, Real Estate and Construction, and content analysis of the material collected through interviews with specialists in public procurement. We defined dimensions of analysis, categorized data and created units of analysis, in an initial data coding matrix, and systematizing the interviews in recording units. The qualitative methodology aims to understand and describe phenomena and can use the participants' perceptions and experiences to understand the multiple realities. Regarding the results, this work made it possible to verify that the transparency of procurement processes has been increasing, however, there are points for improvement, and that the opening to competition, by the contracting entities, has had a favourable evolution, but it can obtain superior results, as there is an excessive use of the direct award. Increased competition and greater transparency in the use of public money are benefits from the implementation of the Public Contracts Code, driven by the obligation to advertise public contracts on the BASE portal and by electronic public procurement.